Analisis Program Adiwiyata untuk Menumbuhkan Karakter Peduli Lingkungan di Sekolah Dasar - Juanah (Universitas Sarjanawiyata Tamansiswa, 2022)
Abstract: This study aims to determine, to find out the management of the Adiwiyata program, the creativity and innovation carried out, the supporting and inhibiting factors and their solutions at SD Negeri Kemirirejo 1. This study uses a descriptive qualitative approach. Data collection techniques using observation, interviews, and documentation studies. The results of the study show that the Adiwiyata program implemented at SDN Kemirirejo 1 since 2017 consists of 4 components, namely: 1) Environmentally Friendly Policies; 2) Implementation of Environment-Based Curriculum; 3) Participatory-Based Environmental Activities; 4) Management of Environmentally Friendly Supporting Facilities through the management functions of Planning, Organizing and Implementing, Monitoring and Evaluation, is well implemented. The results of the adiwiyata program are that in 2018 it was recognized as an adiwiyata school at the Magelang City level and in 2019 as an adiwiyata school at the Central Java province level. The year 2020 is progressing towards the title of a national level Adiwiyata school, but due to the pandemic, this activity has been postponed. The behavior/character possessed by school residents, especially students, shows the formation of a positive character, caring and loving the environment. Adiwiyata's supporting factors are mainly support from school members and committees/parents as well as school policies in the form of vision, mission and funding listed in the RKAS. The teacher carries out an environment-based learning process. Keywords: analysis, adiwiyata program, environmental care character.